Zastosowanie chromotografii gazowej do analiz prostych, nieorganicznych związków azotu i siarki w powietrzu i gazach odlotowych - Gąsiorek, Marek (Zielona Góra: Uniwersytet Zielonogórski)
The possibilities ot the gas chromatography method for qualitative and quantitative analysis of some simple, inorganic nitrogen compounds (N2O, NO, NO2, NH3) and sulphur compounds (SO2, CS2, COS, H2S) were shown. The large utility of this method for analysis of above mentioned compounds in the presence of oxygen, nitrogen, carbon oxides, water vapour etc, was indicated.
Keywords: chromatografia gazowa; siarka - związki; azot - związki